CH3D photomixing spectroscopy up to 2.5 THz: New set of rotational and dipole parameters, first THz self-broadening measurements. (March 2017) - Bray, Cédric; Cuisset, Arnaud; Hindle, Francis; Bocquet, Robin; Mouret, Gaël; Drouin, Brian J.
Abstract: Several previously unmeasured transitions of 12 CH3 D have been recorded by a terahertz photomixing continuous-wave spectrometer up to Q R (10) branch at 2.5 THz. An improved set of rotational constants has been obtained utilizing a THz frequency metrology based on a frequency comb that achieved an averaged frequency position better than 150 kHz on more than fifty ground-state transitions. A detailed analysis of the measured line intensities was undertaken using the multispectrum fitting program and has resulted in a determination of new dipole moment parameters. Measurements at different pressures of the Q R (7) transitions provide the first determination of self-broadening coefficients from pure rotational CH3 D lines. The THz rotational measurements are consistent with IR rovibrational data but no significant vibrational dependence of self-broadening coefficient may be observed by comparison. Highlights: 12 CH3 D spectra measured with a photomixing cw-THz spectrometer. Rotational transitions of 12 CH3 D up to Q R (10) branch at 2.5 THz. Improved set of ground state rotational constants. Determination of new effective dipole moment parameters. Self-broadening coefficients of the pure rotational Q R (7) transitions.